Vaccination in palliative care - Nitsch-Osuch, Aneta (Medycyna Paliatywna/Palliative Medicine, 2019)
Vaccinations are the most effective way to prevent selected infectious diseases. Is there a time and place for vaccinations in palliative medicine? The answer to this question is definitely positive. Vaccinations should be carried out on medical personnel and persons forming close contact with patients, and everybody who takes care of the patients, thus ensuring protection against illnesses and their complications in vaccinated people but also minimising the risk of transmission of infection in the patient’s environment (the so-called cocoon strategy of vaccination that mainly involves vaccination against influenza and pertussis). The vaccination schedule for palliative care patients should be based on the patient’s health condition; the most important seems to be influenza vaccination, which is safe and effective also in palliative care patients. Vaccination for influenza in patients requiring palliative care is effective and safe (use of an inactivated vaccine is recommended; use of vaccine containing live attenuated influenza viruses is contraindicated). Obligatory vaccinations in accordance with the national immunisation schedule program and recommended vaccinations (e.g. against influenza) must be carried out for children who are in close contact with patients. Adults caring for patients should be vaccinated against hepatitis B. Medical staff caring for patients should be vaccinated against hepatitis B (three doses, 0-1-6-month schedule), influenza (one dose every season), and pertussis (one dose every 10 years). Vaccination of personnel is advisable for ethical, epidemiological, and organisational reasons (providing reduction of sickness absence days, lower transmission of influenza viruses in the population, and better health of family contacts of patients).